Pelatihan Pengembangan Jaringan Pemasaran Produk UMK Berbasis Digital pada Kelompok UMK Desa Terusan Kecamatan Maro Sebo Ilir Kabupaten Batang Hari - Sumarni Sumarni; Zulfina Adriani; Ovie Yanti; Wahyu Juari Setiawan; Al Paruk (Nusantara Mengabdi Kepada Negeri, 2024)
UMKM is one of the sectors that contribute to supporting the economy, given its labor-intensive nature. UMKM can effectively create jobs according to the abilities and skills of the community. One such group is the UMK group in Terusan Village, Maro Sebo Ilir District, which is known for its various types of traditional cakes, such as Cepak Kapung, Pedamaran, Engkak, Lapis Agar, Roti Kecik, Kue Bangkit, and various other snacks. The various products of the UMK in Terusan village administratively meet the standards set by the government, starting from business permits in the form of NIB and PIRT to halal certificates, which are facilitated by students through the Village Community Empowerment Program (P2MD) in 2023. However, the challenges faced by the UMKM Terusan Village are in terms of marketing their products. Marketing is still limited to local areas by word of mouth and is usually seasonal. This training can contribute to the development of a marketing network for UMK products in Terusan Village through the use of digital technology.